Secondary confession as the nature of market economy - Рибалкін, В. О. (Proceedings of National Aviation University (archive), 2003)
Approach to clarify the term “market” from theory of ownership’s point of view is offered in this article. It is shown that market economy (market) is relations of secondary confession system. The contents of market economy as relations of secondary confession system (alienation-confession) gives transitional society an opportunity to form the economic system. That system should give a chance to achieve the main reforms’ objectives - to provide society with high production efficiency and social justice. In order to implement it in practice we should have a special state economic policy. This policy'refers to different forms of ownership which have the unity of labor and ownership